Recommendations for the prevention of adverse events in endotracheal suctioning - integrative review - Ana Sabrina Sousa; Cândida Ferrito; José Artur Paiva (Universidade Católica Portuguesa, Instituto de Ciências da Saúde, 2018)
Introduction: The use of endotracheal suctioning is a common procedure in intensive care units, which implies various risks, namely hypoxemia, atelectasis, arterial hypertension, microbial colonization, etc. Nevertheless, healthcare professionals can adopt certain strategies to prevent these adverse events. Aim: To describe good practice relating to endotracheal suctioning in patients undergoing invasive ventilation. Materials and Methods: Integrative literature review. The research occurred in December 2015, using the databases B-on, PUBMED and RCAAP and 534 documents were found. After inclusion/exclusion and quality criteria evaluation, four studies were accepted for inclusion in this review. Results: Recommendations encountered were: suction only when necessary, pre-oxygenate, use a suction catheter with half the diameter of the endotracheal tube, avoid saline instillation, employ a closed aspiration system when FiO2 or positive end-expiratory pressure is elevated, limit the procedural duration to under 15 seconds and monitor the patient. Conclusion: The review demonstrates that some conclusions are not consensual, which represents a limitation of this study, since more experimental studies are needed, which represents a limitation of this study, since more experimental studies are needed. However, the stimulation of open debate, reflection, as well as the adoption of preventative measures, can lead to safer practice.